Fate and Freedom in Korean Historical Films - Hwang, Kyung Moon. author. aut Link
XIX, 255 p. 32 illus. in color.
Keywords: This open access book examines the depiction of Korean history in recent South Korean historical films. Released over the Hallyu (“Korean Wave”) period starting in the mid-1990s, these films have reflected, shaped, and extended the thriving public discourse over national history. In these works, the balance between fate and freedom—the negotiation between societal constraints and individual will, as well as cyclical and linear history—functions as a central theme, subtext, or plot device for illuminating a rich variety of historical events, figures, and issues. In sum, these highly accomplished films set in Korea’s past address universal concerns about the relationship between structure and agency, whether in collective identity or in individual lives. Written in an engaging and accessible style by an established historian, Fate and Freedom in Korean Historical Films offers a distinctive perspective on understanding and appreciating Korean history and culture. Kyung Moon Hwang is Korea Foundation Professor at the Australian National University, Canberra. He is the author of A History of Korea (Third Edition, 2021), Past Forward: Essays in Korean History (2019), Rationalizing Korea: The Rise of the Modern State (2015), and Beyond Birth: Social Status in the Emergence of Modern Korea (2004).